The Religious Divide in Voting Preferences and Attitudes in the 2019 Election. (December 2019) - Sardesai, Shreyas
This article attempts to empirically test the claims made by several commentators that religious polarization was at the core of the 2019 Lok Sabha election verdict. Relying heavily on the National Election Study (NES) data sets, it finds that the election result was in large measure an outcome of massive vote consolidation on religious lines, with the majority Hindu community preferring the Bharatiya Janata Party (BJP)-led National Democratic Alliance (NDA) in unprecedented proportion and the main religious minorities largely staying away from it, although there were some exceptions. It shows that, for two national elections in a row, the Narendra Modi- and Amit Shah-led BJP has been able to overcome the caste hierarchies among Hindus and systematically construct a Hindu category of voters versus others. This chasm between Hindus and the minorities is also seen with respect to their attitudes regarding the government, its leadership and contentious issues like the Ayodhya dispute. This article, however, does not find sufficient evidence with regard to the claims that a large part of the Hindu support for the BJP-led alliance may have been on account of anti-minority sentiments.